Pengaruh Air Cucian Beras Terhadap Pertumbuhan Tanaman Kangkung (Ipomoea Reptans) - Fince Mega Ceria Ziliwu (Jurnal Ilmu Pertanian dan Perikanan, 2025)
This study aims to determine the effect of rice washing water on the growth of water spinach (Ipomoea reptans). Water spinach is a fast-growing leafy vegetable that is widely consumed by the Indonesian population. Rice washing water is a household waste that contains essential nutrients such as nitrogen, phosphorus, potassium, and vitamin B, which can be utilized to fertilize plants. The study was conducted over five days by watering water spinach plants daily using rice washing water. The results showed that water spinach watered with rice washing water grew faster compared to normal conditions, reaching a height of 6 cm on the fifth day. This indicates that rice washing water has a positive effect on plant growth.